Menurunnya Kepedulian Masyarakat dalam Pelestarian Cagar Budaya Tarn an sari - INDRO SULISTYANTO (Jurnal Teknik Sipil dan Arsitektur, 2008)
Cultural Situs Pledge ofTamansari have high history value, as unlocked out by shares existence of Kraton Yogyakarta, what initially personate King place and Consanguinity of Kraton rest and 'mesanggrah' (mind rest). Cultural Situs Pledge ofTamansari become uniquely, because pickings of artefac existing mix one each others with growth of business activity and housing around him, especially the him of with cultural area and visit area ofwisata in Kraton Yogyakarta Area. Development effort and continuation ofsetlement environment around Cultural Pledge of Tamansari Kraton Yogyakarta, expanding in an dynamic life structure, becoming properties of culture which still awake at each setlement community. Properties of the culture among others is artistic potency of Grafting; potency processing of traditional food; artistic potency of show (artistic which take root from heal society); potency of social movement; and history potency, in the form of history situs and a period of movement. Setlement and Cultural Pledge ofTamansari basically is unity of structure life, social-economic-culture structure, and expected society view can live to adjoin (culture living). This condition later of member instruct at one particular logical consequence of development of Cultural Pledge conservation and setlement continued Tamansari, by 'soul' life and management ofyag base on society (community-based management) becoming output of activity of research of Correlation among Friction of Behavior of Society in Development and Development of Self-Supporting Setlement to Cultural Effort Conservation Building Pledge, Case Study: Cultural Area Pledge of Tamansari Kraton Yogyakarta. Â